The roles of chemokines following intracerebral hemorrhage in animal models and humans - Wang, Jinjin; Bian, Liheng; Du, Yang; Wang, Dandan; Jiang, Ruixuan; Lu, Jingjing; Zhao, Xingquan (Frontiers in Molecular Neuroscience, 2023)
Intracerebral hemorrhage (ICH) is one common yet devastating stroke subtype, imposing considerable burdens on families and society. Current guidelines are limited to symptomatic treatments after ICH, and the death rate remains significant in the acute stage. Thus, it is crucial to promote research to develop new targets on brain injury after ICH. In response to hematoma formation, amounts of chemokines are released in the brain, triggering the infiltration of resident immune cells in the brain and the chemotaxis of peripheral immune cells via the broken blood–brain barrier. During the past decades, mounting studies have focused on the roles of chemokines and their receptors in ICH injury. This review summarizes the latest advances in the study of chemokine functions in the ICH. First, we provide an overview of ICH epidemiology and underlying injury mechanisms in the pathogenesis of ICH. Second, we introduce the biology of chemokines and their receptors in brief. Third, we outline the roles of chemokines in ICH according to subgroups, including CCL2, CCL3, CCL5, CCL12, CCL17, CXCL8, CXCL12, and CX3CL1. Finally, we summarize current drug usage targeting chemokines in ICH and other cardio-cerebrovascular diseases. This review discusses the expressions of these chemokines and receptors under normal or hemorrhagic conditions and cell-specific sources. Above all, we highlight the related data of these chemokines in the progression and outcomes of the ICH disease in preclinical and clinical studies and point to therapeutic opportunities targeting chemokines productions and interactions in treating ICH, such as accelerating hematoma absorption and alleviating brain edema.